THE IMPLEMENTATION OF PROOF SYSTEM IN THE CRIMINAL ACT OF DOMESTIC VIOLENCE - Ayu Astari, Sindi; Harefa, Beniharmoni (Awang Long Law Review, 2021)
Domestic Violence is any act committed against a person, resulting in the onset of physical, sexual, psychological, and/or domestic abuse. As we understand it, domestic violence crimes are common in the personal sphere and often lead to the absence of witnesses other than victims who make it difficult to prove. This research aims to determine the regulations related to the settlement of domestic violence and to find out the application of the system of proving domestic violence crimes. This research was conducted by normative juridical research methods. The legal source used is a secondary legal source. The approach used is the statute approach and case approach related to the problem. The results of this study explain that the regulation stipulated in the domestic violence crime stipulated in The Law of the Republic of Indonesia No. 24 of 2004, in establishing a person to be a defendant in a domestic violence crime with the testimony of one witness and supported by one other valid evidence, is proven by the Verdict No. 131/Pid.Sus/2017/PN Pre.